Implementation of Augmented Reality Technology in History Learning: Experimental Study - Apriyanto Apriyanto; Kailie Maharjan; Zhang Wei (Journal of Computer Science Advancements, 2024)
The integration of technology into education continues to evolve, with augmented reality (AR) emerging as a promising tool in enhancing learning experiences. In the context of history education, traditional methods often struggle to engage students and provide immersive experiences. This study investigates the implementation of augmented reality technology in history learning to assess its impact on student engagement and understanding. The research aims to determine whether AR can effectively improve students' comprehension of historical events and concepts compared to conventional teaching methods. A mixed-methods experimental design was employed, involving a sample of high school students who were divided into an experimental group using AR technology and a control group following traditional teaching methods. Data were collected through pre- and post-intervention assessments, surveys, and interviews. The analysis focused on comparing learning outcomes and engagement levels between the two groups. Results indicated that the experimental group demonstrated significantly higher scores on post-intervention assessments and reported greater engagement and interest in the subject matter compared to the control group. These findings suggest that AR technology can enhance students' understanding of historical content by providing interactive and immersive learning experiences. The study concludes that incorporating AR technology into history education can significantly improve student learning outcomes and engagement. The use of AR provides a novel approach to teaching history, offering immersive experiences that can complement traditional methods. Future research should explore the long-term effects of AR on learning and its applicability across various educational contexts.